The Role Of Nationalism In Realizing Social Integration In The Midst Of Ethnic Diversity In Langsa Aceh City - Susilo, Eko; Syafitri, Siska Eka (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2026)
Abstract This study aims to examine the role of nationalism in fostering social integration amidst ethnic diversity in Langsa City, Aceh. Langsa is inhabited by various ethnic groups with distinct cultural backgrounds, presenting challenges related to social conflict due to identity differences. Using a qualitative approach with in-depth interviews and participatory observation, the study reveals that nationalism functions as a moral and social foundation capable of uniting a multi-ethnic society. Consistent with Anderson’s (1983) view that nationalism is an “imagined community” with a powerful social adhesive effect, nationalist values such as love of country, a spirit of togetherness, and respect for diversity strengthen solidarity and tolerance among residents. Furthermore, active community participation in national events serves as an effective medium to reinforce social cohesion. Although challenges such as prejudice and stereotypes persist, inclusive nationalism proves to be a strategic instrument for managing diversity and achieving social harmony. These findings have important implications for the development of educational and social policies that support national integration in other multi-ethnic regions.